Pengaruh Suku Bunga, Jumlah Uang Beredar dan Nilai Tukar Rupiah Terhadap Tingkat Inflasi Provinsi Sumatera Utara Tahun 2012-2021 - Muhammad Bugis; Desry Louhenapessy; Natalia Chrisella Siregar; Selvenco Tuasuun (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2023)
This study aims to analyze the effect between variables both partially and simultaneously on interest rates, amount of money in circulation and exchange rates on the inflation rate in North Sumatra Province in 2012-2021. This research is a research using a quantitative approach. The independent variables in this study are interest rates, money supply and exchange rates. While the dependent variable in this study is inflation. Secondary data collection techniques with quantitative research types obtained from Bank Indonesia, the Central Bureau of Statistics and from related agency sources. This study uses the Error Correction Model (ECM) analysis method. The results showed that the interest rate variable had a positive and signifikan effect on the inflation rate in the long term, whereas in the short term the interest rate had a positive but not signifikan effect on the inflation rate. The money supply variable has a positive and insignifikan effect on the inflation rate in the long and short term. Meanwhile, the exchange rate variable has a negative and insignifikan effect on the inflation rate both in the long term and in the short term.